2011
DOI: 10.1088/0004-637x/729/1/34
|View full text |Cite
|
Sign up to set email alerts
|

Sizes and Temperature Profiles of Quasar Accretion Disks From Chromatic Microlensing

Abstract: Microlensing perturbations to the flux ratios of gravitationally lensed quasar images can vary with wavelength because of the chromatic dependence of the accretion disk's apparent size. Multiwavelength observations of microlensed quasars can thus constrain the temperature profiles of their accretion disks, a fundamental test of an important astrophysical process which is not currently possible using any other method. We present single-epoch broadband flux ratios for 12 quadruply lensed quasars in 8 bands rangi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
264
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(300 citation statements)
references
References 70 publications
(133 reference statements)
32
264
3
Order By: Relevance
“…The maximum likelihood estimate corresponds to = áñ lt-day. However, studies of high-magnification events are likely biased toward small quasar size estimates because it is easier to obtain high magnifications with small sources (e.g., Kochanek 2004;Eigenbrod et al 2008;Blackburne et al 2011). It is also interesting to note that without considering any velocity prior (i.e., adopting a uniform prior), the size determinations of Eigenbrod et al (2008) and Anguita et al (2008) increase by a factor ∼4 (see Sluse et al 2011) but would then require cosmologically unrealistic peculiar velocities for the lens/source.…”
Section: The Observed Magnitude Of Image I=(a B C D) Ismentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum likelihood estimate corresponds to = áñ lt-day. However, studies of high-magnification events are likely biased toward small quasar size estimates because it is easier to obtain high magnifications with small sources (e.g., Kochanek 2004;Eigenbrod et al 2008;Blackburne et al 2011). It is also interesting to note that without considering any velocity prior (i.e., adopting a uniform prior), the size determinations of Eigenbrod et al (2008) and Anguita et al (2008) increase by a factor ∼4 (see Sluse et al 2011) but would then require cosmologically unrealistic peculiar velocities for the lens/source.…”
Section: The Observed Magnitude Of Image I=(a B C D) Ismentioning
confidence: 99%
“…Gravitational microlensing (Chang & Refsdal 1979, 1984; see also Kochanek 2004 andWambsganss 2006) is the main tool used to estimate both parameters, either from time variability or through the wavelength dependence of the microlensing magnification. Microlensing studies (see e.g., Pooley et al 2007;Morgan et al 2010;Blackburne et al 2011Blackburne et al , 2014Blackburne et al , 2015Sluse et al 2011;Jiménez-Vicente et al 2012Hainline et al 2013;Mosquera et al 2013;MacLeod et al 2015) have found that the mean sizes of quasar accretion disks are roughly a factor of 2-3 greater than the predictions of the standard thin disk model. These differences are too large to be explained by contamination from the broad emission lines and the pseudo-continuum contributions, or scattering on scales larger than the accretion disk (Dai et al 2010;Morgan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reverberation mapping establishes the relationship between the size and the luminosity of the BLR and yields a typical BLR size of RBLR ∼ 0.2 pc (Kaspi et al 2007; Chelouche & Daniel 2012) for high redshift luminous quasars. Differential microlensing allows for a constraint on the accretion disk size < ∼ 3 × 10 −3 pc (Blackburne et al 2011;Jiménez-Vicente et al 2012) and for an estimation of the size of the BLR ∼ 0.1 pc (Sluse et al 2011). The observations of gamma-ray emission constrain the size of a jet constituent to a few parsecs (Abdo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mosquera et al (2011) found clear evidence of chromatic microlensing in the "A" component, and provided an estimate of the disk size in the R band in agreement with the simple thin-disk model. Blackburne et al (2011) used the chromatic microlensing to model the accretion disk, and Courbin et al (2010) recalculated the time delays with N-body realizations of the lensing galaxy, which he thought to belong to the "B component" (Δt BA = 8.4, Δt BC = 7.8 and Δt BD = 6.5 days with errors of 25%, 10%, and 11% respectively). Considering multi-color observations of other lensed quasars, a single-epoch multi-band photometry was used on MG0414+0534 to constrain the accretion disk model and the size of the emission region in the continuum Floyd et al 2008).…”
Section: Introductionmentioning
confidence: 99%